Serotoninergic modulation in the brainstem and hypothalamus of female overnourished rats: impact on mitochondrial markers, oxidative stress and BDNF mRNA levels - Thyago de Oliveira Rodrigues; Osmar Henrique dos Santos Júnior; Maria Daniele Teixeira Beltrão de Lemos; Matheus Santos de Sousa Fernandes; Fatma Hilal Yagin; Burak Yagin; Samarjit Das; Abdullah F. Alghannam; Pablo Prieto-González; Claudia J. Lagranha; Claudia J. Lagranha (Frontiers in Molecular Biosciences)
IntroductionObesity is a global epidemic identified by the World Health Organization, and its complexity involves genetic, cultural, socioeconomic, and behavioral factors.MethodsIn this study, we used female Wistar rats, with litters standardized to nine female pups, which were divided into two groups: normally nourished or overnourished. The groups were further subdivided into control and fluoxetine-treated groups, with the pharmacological treatment maintained until the 21st day of life. At 30 days of age, euthanasia was performed, and tissues from the hypothalamus and brainstem were collected.ResultsWe observed an increase in body weight and the Lee index in the overnourished group, but fluoxetine treatment reduced these indices. Additionally, overnourished rats consumed more palatable food. Biochemically, NADH content in the hypothalamus was altered by overnutrition but restored by fluoxetine treatment. Citrate synthase activity was reduced in the overnourished group in the hypothalamus but increased in the brainstem of fluoxetine-treated rats. The production of reactive oxygen species was higher in the overnourished group, and oxidative stress biomarkers showed increased levels of MDA and protein carbonylation in these rats. Overnutrition impaired the antioxidant activity of enzymes in both the hypothalamus and brainstem, whereas fluoxetine treatment improved this activity. BDNF expression was higher in the fluoxetine-treated groups compared to the overnourished group.DiscussionThese results demonstrate the detrimental effects of maternal overnutrition on the development of female offspring and the therapeutic potential of serotonergic manipulation to mitigate the early effects of obesity, with tissue-specific variations.